PERAN MANAJEMEN KASUS DALAM PERAWATAN IBU HAMIL BERISIKO TINGGI - Meyana Marbun; Keysha Iszmi Erhan; Amanda Sahfitri (Jurnal Minfo Polgan, 2022)
High-risk pregnancy requires intensive monitoring, multiple interventions, and complex care coordination to ensure optimal outcomes for both mother and fetus. In this context, case management has emerged as a crucial strategy for integrating health, social, and psychological services. This literature review examines the definition and principles of case management, the specific role of case managers in the care of high-risk pregnant women, and the benefits and challenges of its implementation. The goal is to highlight how case management can improve care coordination, service accessibility, and patient satisfaction, ultimately contributing to reduced maternal and perinatal morbidity and mortality.